Dehydroepiandrosterone-Sulfate, Insulin Resistance and Ovarian Volume Estimation in Patients With Polycystic Ovarian Syndrome - Chrysi Christodoulaki; Eftihios Trakakis; Vasilios Pergialiotis; Periklis Panagopoulos; Charalampos Chrelias; Dimitrios Kassanos; Dimos Sioutis; Nikolaos Papantoniou; Dimitrios Xirofotos (Tehran University of Medical Sciences, 2017)
Objective: To investigate the potential association of DHEA-S with metabolic and hormonal alterations and with disorders of ovarian morphology. Materials and methods: The present study was based on women with PCOS that attended the Gynaecological Endocrinology - Paediatric and Adolescence Endocrinology Department of our clinic. Overall, 321 patients who met the Rotterdam ESHRE/ ASRM - Sponsored criteria for the definition of PCOS were included. Women's personal medical history was recorded, anthropometric parameters were assessed and blood was drawn for analysis of metabolic and hormonal parameters. A gynaecological ultrasound was also performed to evaluate ovarian morphology. Results: Correlation analysis revealed a significant negative correlation of DHEA-S with the mean volume of the right and left ovary and with the maximum volume of the largest ovary. This finding remained significant after adjusting for age and BMI (β ± SE = -0.39 ± 0.17, p = 0.023 in the case of mean ovarian volume and β ± SE = -0.36 ± 0.17, p = 0.032 in the case of the maximum volume of the maximum ovarian volume). Conclusion: The findings of our study reveal a clear negative association of DHEA-S with ovarian volume. To date, however, current evidence in this field are restricted to experimental animal models. Future clinical studies are needed in this field to corroborate our findings.